Feasibility of spatially-offset Raman spectroscopy for in-vitro and in-vivo monitoring mineralisation of bone tissue-engineering scaffolds - Liao, Zhiyu; Sinjab, Faris; Nommeots-Nomm, Amy; Jones, Julian; Ruiz-Cantu, Laura; Yang, Jing; Rose, Felicity R.A.J.; Notingher, Ioan (American Chemical Society, 2017)
We investigated the feasibility of using spatially-offset Raman spectroscopy (SORS) for non-destructive characterisation of bone tissue engineering scaffolds. The deep regions of these scaffolds, or scaffolds implanted subcutaneously in live animals, are typically difficult to measure by confocal Raman spectroscopy techniques because of the limited depth penetration of light caused by the high level of light scattering. Layered samples consisting of bioactive glass foams (IEIC16), 3D-printed biodegradable poly-(lactic-co-glycolic acid) scaffolds (PLGA) and hydroxyapatite powder (HA) were used to mimic non-destructive detection of bio-mineralisation for intact real-size 3D tissue engineering constructs. SORS spectra were measured with a new SORS instrument using a digital micro-mirror device (DMD) to allow software selection of the spatial offsets. The results show that HA can be reliably detected at depths of 0-2.3 mm, which corresponds to the maximum accessible spatial offset of the current instrument. The intensity ratio of Raman bands associated to the scaffolds and HA with the spatial offset depended on the depth at which HA was located. Furthermore, we show the feasibility for in-vivo monitoring mineralisation of scaffold implanted subcutaneously by demonstrating the ability to measure transcutaneously Raman signals of the scaffolds and HA (fresh chicken skin used as a top layer). The ability to measure spectral depth profiles at high speed (5 s acquisition time), and the ease of implementation, make SORS a promising approach for non-invasive characterisation of cell/tissue development in-vitro, and for long-term in-vivo monitoring the mineralisation in 3D scaffolds subcutaneously implanted in small animals.